Arrange these functions from the greatest to the least value based on the average rate of change in the specified interval.
Tiles
f(x) = x2 + 3x
interval: [-2, 3]f(x) = 3x - 8
interval: [4, 5]f(x) = x2 - 2x
interval: [-3, 4]
f(x) = x2 - 5
interval: [-1, 1]
Sequence

>

>

>


Respuesta :

we know that

The Average Rate of Change is the slope of a line or a curve on a given range. It is defined as the ratio of the difference in the function f(x) as it changes from 'a' to 'b' to the difference between 'a' and 'b'.

So

[tex] A=\frac{(f(b)-f(a))}{(b-a)} [/tex]

case a) [tex] f(x) = x^{2} + 3x [/tex]

in the interval [tex] [-2, 3] [/tex]

[tex] a=-2\\ b=3\\ f(a)=(-2)^{2} +3*(-2)\\ f(a)=-2\\ f(b)=(3)^{2} +3*(3)\\ f(b)=18 [/tex]

Find the Average Rate of Change

[tex] A=\frac{(18-(-2))}{(3+2)} [/tex]

[tex] A=\frac{20}{5} [/tex]

[tex] A=4 [/tex]

case b) [tex] f(x) = 3x-8 [/tex]

in the interval [tex] [4, 5] [/tex]

[tex] a=4\\ b=5\\ f(a)=3*4-8\\ f(a)=4\\ f(b)=3*5-8\\ f(b)=7 [/tex]

Find the Average Rate of Change

[tex] A=\frac{(7-(4))}{(5-4)} [/tex]

[tex] A=\frac{3}{1} [/tex]

[tex] A=3 [/tex]

case c) [tex] f(x) = x^{2} -2x [/tex]

in the interval [tex] [-3, 4] [/tex]

[tex] a=-3\\ b=4\\ f(a)=(-3)^{2} -2*(-3)\\ f(a)=15\\ f(b)=(4)^{2} -2*(4)\\ f(b)=8 [/tex]

Find the Average Rate of Change

[tex] A=\frac{(8-(15))}{(4+3)} [/tex]

[tex] A=\frac{-7}{7} [/tex]

[tex] A=-1 [/tex]

case d) [tex] f(x) = x^{2} -5 [/tex]

in the interval [tex] [-1, 1] [/tex]

[tex] a=-1\\ b=1\\ f(a)=(-1)^{2} -5\\ f(a)=-4\\ f(b)=(1)^{2} -5\\ f(b)=-4 [/tex]

Find the Average Rate of Change

[tex] A=\frac{(-4-(-4))}{(1+1)} [/tex]

[tex] A=\frac{0}{2} [/tex]

[tex] A=0 [/tex]

Arrange these functions from the greatest to the least value based on the average rate of change in the specified interval

so

the answer is

1) [tex] f(x) = x^{2} + 3x [/tex] -------> [tex] A=4 [/tex]

2) [tex] f(x) = 3x-8 [/tex] -----> [tex] A=3 [/tex]

3) [tex] f(x) = x^{2} -5 [/tex] -----> [tex] A=0 [/tex]

4) [tex] f(x) = x^{2} -2x [/tex] -----> [tex] A=-1 [/tex]

Answer:

b,d,c,a

Step-by-step explanation:

a) [tex]f(x) = x^2 + 3x[/tex]

interval: [-2, 3]

Average value = [tex]\frac{f(b)-f(a)}{b-a}[/tex]

=[tex]\frac{f(3)-f(-2)}{3-(-2)} =\frac{18+2}{5} -4[/tex]

b) [tex]f(x) = 3x - 8[/tex]

interval: [4, 5]

Average value =[tex]\frac{15-7}{1} =8[/tex]

c)

[tex]f(x) = x^2 - 2x[/tex]

interval: [-3, 4]

Average value =[tex]\frac{8-15}{7} =-1[/tex]

d) [tex]f(x) = x^2 - 5[/tex]

interval: [-1, 1]

Average value =[tex]\frac{-4+4}{2} =0[/tex]

Hence arranging we get

b, d, c, a

ACCESS MORE